(untitled) (Argos, 2026)
The figure of the oracle has been used throughout Greek tragedy as a means of communication for the divine voice. In Greek literature, one of its most prominent representatives has been Cassandra, the Trojan prophetess. This work explores the function of her prophecy in Aeschylus’ Agamemnon (vv. 1072-1177), and how this same story is reconfigured in Lycophron’s Alexandra, specifically the story of her death (vv. 1099-1122). On the one hand, in Aeschylus’ tragedy, the oracle is the axis around which the tragic conflict develops, occupying a prominent place at key moments in the work and projecting its influence onto the other tragedies that make up the linked trilogy of the Oresteia. On the other hand, in Alexandra, the prophetic discourse is the voice of Cassandra, which, in addition to extending to almost the entire poem, is not a resource for a specific moment in relation to someone else’s tragedy, but rather Lycophron transforms the Aeschylean material and gives the figure of Cassandra a greater degree of prominence to narrate her own story.